Mergers and acquisitions : an Oil & Gas Equipment Sector case study Siemens' acquisition of Dresser-Rand - Scharf, Andreas (2015)
In September 2014, the German engineering and manufacturing company Siemens announced the plan to acquire the American manufacturer of oil and gas equipment and service provider, Dresser-Rand for $83 a share. In a standalone valuation, Siemens can be valued between € 87 and €104 and tends to be undervalued. Contrarily, Dresser-Rand appears to be overvalued, since the current market price of $68 is at the upper valuation range of $36 to $88.1 Additional revenues and reduced costs, ex transaction and implementation costs are worth $141 to $458 million and may add synergies of $1.8 to $6 a share to the standalone value of Dresser-Rand. Despite the fact that Dresser-Rand fits into Siemens’ Power and Gas division from a strategic point of view and that the M&A sentiment is currently beneficial to tap into the M&A market, an acquisition price of $83 seems to be fairly high. Siemens should not realize the deal and offer a premium of 21% to the current market price. The thesis recommends an acquisition price range of $47 to $73.2 This case study shows that the world of M&A is fascinating, but also complex. Bid-prices and valuations often substantially diverge – depending on the strategic fit and potential synergies. The thesis mentions shareholder pressure, unsuccessful recent acquisition activities, legal & technological burden, high cash balances and personal interests as reasons for Siemens’ high premium.